Strategi Pengelolaan Lahan Peternakan Berkelanjutan dalam Menghadapi Alih Fungsi Lahan Menjadi Perumahan Di Kecamatan Bawen - Devi Kusuma Pradana; Dewi Lestari; Reni Dwi Agustin (Universitas Muhammadiyah Kotabumi, 2026)
The conversion of agricultural and livestock land into non-agricultural uses, particularly residential areas, has continued to increase in line with population growth and the expansion of peri-urban regions. Bawen District, a strategic area in Semarang Regency, is experiencing significant land-use pressure, resulting in a decline in productive land and posing a threat to the sustainability of livestock farming. This study aims to identify respondent characteristics, analyze internal and external factors, and formulate priority strategies for sustainable livestock land management. The research was conducted from July 25 to September 2, 2025, using observation, in-depth interviews, and literature review, with purposive sampling applied to 24 affected farmers. Data were analyzed using the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), SWOT, and IE matrices. The results indicate that most respondents are over 40 years old, have more than 10 years of farming experience, and are predominantly engaged in goat farming. The IFE score of 1.351 and the EFE score of 1.551 place the strategy in Quadrant I (aggressive position). The recommended priority strategy is the SO strategy, which includes optimizing farmers’ experience, promoting crop–livestock integration (zero waste farming), strengthening farmer groups, and applying alternative feed technologies such as fermentation, silage, and hydroponic fodder systems. These strategies are expected to enhance production efficiency and support the sustainability of livestock farming amid the increasing rate of land conversion.